II - Hospital morbidity by lesions and poisonings - Lebrão, Maria Lúcia (1997)
Today in Brazil the "Hospital Internment Authorizations" (AIH) represents about 80% of the total internments in the country and constitutes a data base of easy access available in CD-ROM. This high coverage allows one to draw a reasonable picture, close to reality, of the morbidity demanding hospitalization. Among the causes there is the diagnostic category lesions and poisonings noteworthy for severity and frequency. Hospital internments by this diagnostic category occurring in a month in 1994 have been focused on. Some epidemiological and hospital use characteristics, such as demographic aspects, specific diagnostic category, lenght of stay and mortality are described. It was observed that lesions and poisonings accounted for 5% to 6% of all hospital internments in the country, being predominantly among men under 65 of age. This diagnostic category was the first cause of hospital internments among men of from 15 to 29 years of age. Fractures were the most frequent specific diagnosis (about 37.5%), almost all of them involving members (legs or arms). The injuries were mainly located in hands, arms, head and neck and occurred predominantly among young men, leading to the believe that they were due to work or traffic accidents. Regarding burns, the fregment occurrence among children under 5 years of age is worthy of note. The authors lament the lack of information as to their causes such as would enable appropriate preventive actions to be taken.